Preliminary data about the avifauna of the Thai Nguyen province - Thuy, Le Dinh (Academia Journal of Biology, 2014)
Surveys on the birds of the Thainguyen province were carried out for two years 2004 and 2005. 138 bird species belonging to 45 families and 15 orders were recorded. Among them, 4 threatened species were listed in the Red Data Book of Vietnam, 2000: Lophura nycthemera, Bubo zeylonensis, Phodius badius, Aerodramus brevirostris. Also, there were 9 species listed in the Decree No 32/2006/ND-CP of the government: 2 species in group IB (strictly prohibited on exploitation and use) and 7 species in the Group IIB (limited on exploitation and use). The bird species numbers recorded at four habitats were different. The hill and soil moutain habitats had the highest species number (105 species, at 76% of the total species). The lake, river, tream and resident habitat had the lowest species number (50 species, 36% of the total species).